On-road assessment of fitness-to-drive in persons with MS with cognitive impairment: A prospective study. (October 2018) - Morrow, Sarah A; Classen, Sherrilene; Monahan, Miriam; Danter, Tim; Taylor, Robert; Krasniuk, Sarah; Rosehart, Heather; He, Wenqing
Background: Cognitive impairment is common in multiple sclerosis (MS). In other populations, cognitive impairment is known to affect fitness-to-drive. Few studies have focused on fitness-to-drive in MS and no studies have solely focused on the influence of cognitive impairment. Objective: To assess fitness-to-drive in persons with MS with cognitive impairment and low physical disability. Methods: Persons with MS, aged 18–59 years with EDSS ⩽ 4.0, impaired processing speed, and impairment on at least one measure of memory or executive function, were recruited. Cognition was assessed using the Minimal Assessment of Cognitive Function battery. A formal on-road driving assessment was conducted. Chi-square analysis examined the association between the fitness-to-drive (pass/fail) and the neuropsychological test results (normal/impaired). Bayesian statistics predicting failure of the on-road assessment were calculated. Results: Of 36 subjects, eight (22.2%) were unfit to drive. Only the BVMTR-IR, measuring visual-spatial memory, predicted on-road driving assessment failure ( X 2 ( df = 1, N = 36) = 3.956; p = 0.047) with a sensitivity of 100%, but low specificity (35.7%) due to false positives (18/25). Conclusion: In persons with MS and impaired processing speed, impairment on the BVMTR-IR should lead clinicians to address fitness-to-drive.